THE RELIABILITY OF 3D CBCT IN ASSESSING THE AIRWAY VOLUME AMONG PATIENTS WITH CLASS III MALOCCLUSION - Dr Vidya B, Dr Suma M S, Dr Shanthala, Dr Rakshita Jagadish Baseganni, Dr Varsha Patel G B, Dr Kritika Raj (South Eastern European Journal of Public Health, 2025)
Introduction: The pharyngeal airways play an important role in respiration, deglutition, phonation and important in the growth and development of craniofacial skeleton. Alteration in the craniofacial skeleton leads to obstruction of pharyngeal airway which leads to class II and class III malocclusion. Thus the aim of the present study was to evaluate the impact of 3D CBCT to assess class III malocclusion on oropahrygneal and nasopharyngeal airways. Materials and methods: The cross sectional, prospective study was conducted on a total 60 patient was divided into 2 groups. Group A comprised of 30 patients with class I and group B 30 patients with class III malocclusion. The patients were in the age range of 20-35yrs with BMI 18.5-29.9. The images of pharyngeal airway spaces were recorded using CBCT and or Oropharyngeal airways (OPV), Nasopharyngeal airways (NPV), vertical height of oropharynx (HOP), Constricted minimum axial area (CMinAx), and Constricted posterior airway space (CPAS) were measured. The difference between the two groups was determined by using ANOVA test and the correlation of variables were assessed using Pearson's correlation. Results: OPV in class I was 829±1786.59 and in class III was 10941.43±2863.22 with p value of <0.001. For NPV in class I, 9889.57±2274.40 and class III 8166.30±1673.94 with p value of 0.03 (significant). For HOP in class I, 41.08±4.50 and class III 44.43±4.10 with p value of 0.08 (non-significant). For CMinAx in class I, 152.15±71.74 and class III 249.91±170.98 with a p value of 0.008 (significant). For CPAS in class I 6.83±2.46 and class III 10.01±4.94 with p value of 0.02 (significant). The mean and standard deviation for BMI was 23.23±1.76 for class I and 23.46± 2.30 for class III with p value of 0.70. In class I there was a positive correlation with NPV and CMinAx), whereas in Class III there was a positive correlation with NPV, CMinAx and CPAS. Conclusion: The constricted minimum axial area was the predictor variable that best explained the Oropharyngeal airway volume. 3D CBCT provides a low-radiation rapid scan capability to assess patients airway using highly correlative linear, cross-sectional area, and volumetric measurements that include assessing the morphometry of the airway in three dimensional view helps in their accurate assessment.